The role of tutor's questioning in mentoring learners' responses to and uptake of feedback on writing - Saeed, Murad Abdu; AbuSa’aleek, Atef Odeh; Al Qunayeer, Huda Suleiman (Indonesian Journal of Applied Linguistics, 2022)
How teachers can provide effective feedback that promotes' students' active responses to and use of it is the question of the current debate in research. The need for teachers to formulate/compose their feedback in the form of questioning alleviates their authoritative roles in the process. Therefore, this study explored the role of teacher Google Doc-based feedback given in the form of questions on the assignments of 14 pairs of undergraduates in a Malaysian university in fostering their responses to feedback and uptake of it in writing. The results revealed that the feedback questions fall into single Yes/No questions, single Wh-questions, and a combination of both, which served as eliciting responses, eliciting information, seeking clarifications, requesting, checking certainty, and inviting learners to respond to and interact over the e-feedback before using it in revising their texts. Findings indicate that Google Docs functions as an interactive platform where students diversify their responses to e-feedback, such as commenting on the e-feedback, interacting around the e-feedback issues, seeking further feedback, resolving the e-feedback, and addressing the e-feedback through edits/text revisions. Furthermore, the way e-feedback questioning is formulated influences how students respond to and use e-feedback in revising their assignments. The study provides valuable suggestions for teacher feedback practices in graduate courses in higher educational institutions.